Comparative Analysis of Reagents in Gold and Silver Leaching Process Using the Bottle Roll Test Method - Ardiansyah, Rizki; Wisnu Pratami, Nabila Putri; Wirasangka, Zanescaya (Journal of Metallurgical Engineering and Processing Technology, 2025)
According to Law No. 4 of 2009, mineral processing in Indonesia must be carried out domestically. Cyanide (NaCN) remains the primary reagent in gold extraction due to its efficiency, but its negative environmental impact has driven the development of more environmentally friendly alternative reagents, such as thiosulfate and thiocyanate. This study aims to compare three types of reagents, namely NaCN, EG, and LW, in the gold and silver leaching process using the Bottle Roll Test method. The results show that LW achieved the highest gold extraction rate of 94%, followed by NaCN at 92% and EG at 88%. The best reaction kinetics were observed with LW, which reached maximum extraction within 8 hours. In terms of cost, NaCN was the most economical at 11.29 USD/ton of ore, lower than EG at 12.89 USD/ton and LW at 222.82 USD/ton. This study provides guidance for the gold mining industry in selecting the optimal leaching reagent based on extraction efficiency and cost-effectiveness.